Polyacetylenic caffeoyl amides from Ammodaucus leucotrichus. (February 2023) - Hajib, Ahmed; Danton, Ombeline; Keller, Morris; Potterat, Olivier; Bougrin, Khalid; Charrouf, Zoubida; Hamburger, Matthias
Abstract: Six undescribed polyacetylenic caffeoyl amides, five known flavones and three known lignans were obtained from the fruits of the North African traditional medicinal plant Ammodaucus leucotrichus Coss. & Durieu (Apiaceae). Isolation was achieved by a combination of chromatographic methods, and structures were established by extensive 1D and 2D NMR spectroscopy, mass spectrometry, electronic circular dichroism, and by GC-MS analysis of sugar derivatives. Polyacetylenic caffeoyl amides are reported for the first time as specialized metabolites. Graphical abstract: Image 1 Highlights: Six polyacetylenic caffeoyl amides were obtained from the fruits of Ammodaucus leucotrichus . Polyacetylenic caffeoyl amides are reported for the first time as natural products. The chemotaxonomic relevance of polyacetylenic caffeoyl amides is discussed.